The role of internal audit in meeting the requirements of the International Financial Reporting Standard IFRS 17 for Iraqi insurance companies - reality and challenges (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:            The research aims to identify the cognitive aspects of the research variables and verify the impact of applying the requirements of the International Financial Reporting Standard IFRS17 on the current internal audit procedures. These variables were studied in insurance companies listed on the Iraq Stock Exchange. The sample included (5) companies, A checklist was organized to determine the reality of the internal audit procedures and the most important challenges that will face the internal audit procedures if IFRS 17 requirements are applied. The researchers adopted the descriptive and analytical approach and used many statistical methods, namely the arithmetic mean and standard deviation. The researchers reached conclusions, the most important of which was that IFRS17 is one of the important standards that will help organize accounting treatments for insurance contracts. The current internal audit procedures are not qualified to meet the requirements of IFRS17 because they operate in accordance with the requirements of the unified accounting system, which lacks the most basic elements of measurement, presentation, and disclosure that the standard included. The researchers reached recommendations, the most important of which was that it is necessary for the authorities responsible for regulating the profession to amend the requirements of the accounting system. The unified standard to keep pace with the requirements of IFRS17, and the necessity of organizing professional training courses to increase the internal audit team’s knowledge of the requirements of the standard.